What's your favourite? - Drew, David; Stewart, Chantal; Longman (Harlow, England Longman, 1998)
This book encourages children to talk about their favourite things, using repetitive sentence structures and colourful illustrations to build vocabulary and conversational skills.
A beginner-level reader featuring simple text and engaging illustrations to help young learners discuss preferences.
For early readers, ages 5-7.
Keywords: Readers (Primary), English language$1 (BStudy and teaching$1 (BJuvenile literature.s